2000
DOI: 10.1007/s004210000305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dehydration on gastrointestinal function at rest and during exercise in humans

Abstract: Dehydration leads to the aggravation of gastrointestinal (GI) complaints during exercise. The aim of this study was to examine the effect of dehydration on various GI parameters during strenuous exercise. Ten healthy well-trained men were investigated in dehydrated and in euhydrated conditions. Dehydration took place before the experiments using a dehydration regimen in a sauna leading to a 3% loss of body mass. Each experiment consisted of 1 h pre-exercise rest, 1.5 h cycling at 70% maximal exercise intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 21 publications
(23 reference statements)
0
47
0
1
Order By: Relevance
“…We designed our experiment in this manner to increase its internal validity. Both exercise 16,41 and hypohydration 42 can negatively influence the GER of a fluid. If we had added these variables, we might have confounded the results of our original research questions.…”
Section: Discussionmentioning
confidence: 99%
“…We designed our experiment in this manner to increase its internal validity. Both exercise 16,41 and hypohydration 42 can negatively influence the GER of a fluid. If we had added these variables, we might have confounded the results of our original research questions.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Brummer, a significant relationship was observed between humidity and AA, and it was reported, in their study on the physiology of hunger, that a decrease in body fluid loss, fecal stasis, and fecal dehydration prepared the ground for inflammation (Brumer, 1970). In contrast, van Nieuwenhoven et al reported that changes in intestinal system functions such as intestinal permeability and orocaecal transit time were not the reason for dehydration occurring (van Nieuwenhoven et al, 2000). We also determined, during a 4-year (2004-2007) study using meteorological data in our region, that such data as moisture and amount of rain did not have an effect on the frequency of AA (Table 3).…”
Section: Altitude (Meters)mentioning
confidence: 96%
“…In this setting, even small increases in plasma AVP levels can cause significant water retention and hyponatremia, especially in combination with excessive water intake. Furthermore, gastrointestinal blood flow and water absorption from the stomach and intestine may be impaired during exercise (73). When the athlete stops activity, water absorption may increase rapidly and significantly (73).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Furthermore, gastrointestinal blood flow and water absorption from the stomach and intestine may be impaired during exercise (73). When the athlete stops activity, water absorption may increase rapidly and significantly (73). In the setting of elevated AVP levels, this rapid absorption of large quantities of water or hypotonic fluids can lead to significant falls in serum sodium.…”
Section: Pathophysiologymentioning
confidence: 99%